Analisis Bauran Pemasaran Pada Po. Bus Metro Permai Kabupaten Tana Toraja - Jimmy Baan Rantetiku; Dina Ramba; Rati Pundissing (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The aim of the research to be achieved is to analyze marketing Bauranes in PO. Metro Permai Bus Makale Utara District in increasing the number of passengers based on the marketing mix (7P marketing mix). The research method used is descriptive using a qualitative approach to provide an overview of the problem under study. The data analysis technique used is the marketing mix marketing strategy. Then the results obtained by applying the marketing mix mix are obtained that PO. Metro Permai Buses increase consumer interest by providing a variety of products according to customer needs and affordable prices for each type of bus, as for the location of the PO. The Metro Permai bus located in the city center is the right strategy that makes it easier for consumers when they want to buy tickets, making it easier to make payments via transfer so that consumers who are unable to pay can pay via transfer. Keywords: Marketing Mix, 7p, And PO. Permai Metro Buses